Surgery for Spine Disease and Intractable Pain - Boling, Warren W. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book describes the diagnosis and surgical treatment approaches for a number of common and rare painful conditions affecting the brain and spine.